Investigation into Educational Managers’ Level of Confidence and its Role in the Management of Educational Enterprise - Muhammad Arshad Dahar; Khalid Fareed; Rashida Ahmad (UW Journal of Management Sciences, 2022)
Purpose: The paper aims to explore 1) the educational managers’ level of confidence, and 2) the role of confidence in the management of educational enterprise. The idea revolves around the reason that confidence greatly contributes towards the success of any versatile enterprise like education and that lack of confidence on the part of managers may influence the management process adversely. Design/Methodology: The nature of the study is descriptive; therefore, survey method was used. The population comprised the managers of educational enterprise in whole Pakistan. Managers from 4 educational departments at Islamabad were chosen as the sample of the study. The simple random sample technique was used and 40 managers were randomly selected from each department comprising total sample of 160 managers. Questionnaire, comprising 25 close ended questions, was the instrument for data collection. Data were collected personally and then analyzed through statistical calculations and procedures such as mean, percentage, standard deviation and chisquare. MS Excel and Statistical Package of Social Sciences (SPSS) were used to apply the statistical procedures and formulae to analyze the data. Findings: From the results, conclusion is drawn out that educational managers possess the characteristics of confidence to a great extent and that confidence plays a vital role in the management system for sustained success of educational enterprise. Recommendations have also been put forward which may help to boost up managers’ confidence so that they may manage the educational enterprise in a more fruitful manner. Implications: The paper envisages great implications for the managers and the management of educational enterprise. It may serve as a source of motivation for educational managers to further enhance their confidence level and equip themselves with such characteristics and capabilities that they may evolve an effective quality management system for sustained success of educational enterprise.